Determination of secondary ion mass spectrometry relative sensitivity factors for polar and non-polar ZnO - Laufer, Andreas; Volbers, Niklas; Eisermann, Sebastian; Potzger, Kay; Geburt, Sebastian; Ronning, Carsten; Meyer, Bruno K.; Justus Liebig University Giessen (My University, 2011)
Zinc oxide (ZnO) is regarded as a promising material for optoelectronic devices, due to its electronic properties. Solely, the difficulty in obtaining p-type ZnO impedes further progress. In this connection, the identification and quantification of impurities is a major demand. For quantitative information using secondary ion mass spectrometry (SIMS), so-called relative sensitivity factors (RSF) are mandatory. Such conversion factors did not yet exist for ZnO. In this work, we present the determined RSF values for ZnO using primary (ion implanted) as well as secondary (bulk doped) standards. These RSFs have been applied to commercially available ZnO substrates of different surface termination (a-plane, Zn-face, and O-face) to quantify the contained impurities. Although these ZnO substrates originate from the same single-crystal, we observe discrepancies in the impurity concentrations. These results cannot be attributed to surface termination dependent RSF values for ZnO.
Keywords: p-type Zinc oxide (ZnO); identification and quantification of impurities; secondary ion mass spectrometry (SIMS); relative sensitivity factor (RSF); ddc:530